2019
DOI: 10.1002/ptr.6363
|View full text |Cite
|
Sign up to set email alerts
|

Furanodienone overcomes temozolomide resistance in glioblastoma through the downregulation of CSPG4‐Akt‐ERK signalling by inhibiting EGR1‐dependent transcription

Abstract: Glioblastoma multiforme (GBM) is a highly aggressive type of brain tumour. Patients with GBM respond poorly to chemotherapy and have poor survival outcomes. Neuron‐glial antigen 2 (NG2), also known as chondroitin sulphate proteoglycan 4 (CSPG4), has been shown to contribute to critical processes, such as cell survival, proliferation, and chemotherapy resistance, during glioma progression. In this study, we found that furanodienone (FUR), a diene‐type sesquiterpene isolated from the rhizomes of Rhizoma curcumae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 45 publications
2
14
0
Order By: Relevance
“…Activated SHP2 induces activation of the Ras (for rat sarcoma virus)–ErK (extracellular signal-regulated kinases) signaling pathway leading to mitogenic response [ 52 ]. In the nucleus, ERK phosphorylates and activates the transcription activator ELK1 (for E-26-like protein-1) [ 53 ]. Activated ELK1 along with SRF (serum response factor) binds to serum response elements (SREs) and induces the expression of immediate early genes including c-Fos and c-Jun [ 54 56 ].…”
Section: Caga and Gastric Cancermentioning
confidence: 99%
“…Activated SHP2 induces activation of the Ras (for rat sarcoma virus)–ErK (extracellular signal-regulated kinases) signaling pathway leading to mitogenic response [ 52 ]. In the nucleus, ERK phosphorylates and activates the transcription activator ELK1 (for E-26-like protein-1) [ 53 ]. Activated ELK1 along with SRF (serum response factor) binds to serum response elements (SREs) and induces the expression of immediate early genes including c-Fos and c-Jun [ 54 56 ].…”
Section: Caga and Gastric Cancermentioning
confidence: 99%
“…EGR1 is a Cys2-His2-type zinc finger transcription factor that in GB cell lines has been shown to bind to GC-rich sites of the TGF-β promotor leading to decreased proliferation and suppressing transformation [ 68 ]. In contrast, another study showed that EGR1 induces U251 cell migration via activation of fibronectin [ 69 ]; and other reports indicated that EGR1 confers temozolomide resistance in GB [ 70 , 71 ]. EGR1 has also been shown to promote a glioma stem cell-like phenotype [ 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another study aiming to prove the importance of vehicle-specific CAR design, two anti-CD5 CARs with a 4-1BB/CD3ζ (a T cell-associated) or a 2B4/CD3ζ (rather NK cell-specific) intracellular tail were tested [227]. Both were transduced into NK cells and employed in a CD5 + T cell acute lymphoblastic leukemia (T-ALL) mouse model, where they both exhibited specific cytotoxicity and prolonged survival of the mice.…”
Section: B4 (Cd244)mentioning
confidence: 99%
“…Both were transduced into NK cells and employed in a CD5 + T cell acute lymphoblastic leukemia (T-ALL) mouse model, where they both exhibited specific cytotoxicity and prolonged survival of the mice. The 2B4/CD3ζ CAR displayed greater lytic capacity but also elevated toxicity against non-malignant T cells [227].…”
Section: B4 (Cd244)mentioning
confidence: 99%